Is the nutritional status of males and females equally affected by economic growth? Evidence from Vietnam in the 1990s - Vasco Molini; Maarten Nubé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
While the nutritional status of individuals became in recent years a central issue in development economics, relevant and reliable data are often scarce. Available living standard surveys provide a wide set of information about household food consumption and calorie intake. Yet, due to the focus on households, the surveys are, in general, little informative about the intra-household allocations. The present study, after comparing calorie intake and anthropometric measures, proposes the BMI of adult males and females as a useful tool to understand the intra-household allocations and to check whether there is gender discrimination on food access inside the households. Vietnamese data show that anthropometric measures tend to improve less quickly than the calorie intake and males tend to benefit more than females from economic improvements. This tendency is visible in particular in the northern regions, in rural areas and among the poorest quintile of the population. We tested econometrically the robustness of our findings. The results confirm the occurrence of gender discrimination in nutritional status. Moreover, it emerges very clearly that the distribution of the economic improvements inside the households is extremely unfair. The males' BMI growth elasticity to expenditures variation is found to be almost double as compared to the females' one. Also, results confirm that inside the more disfavoured groups (ethnic minorities, northern rural areas) females are even more discriminated and show a very poor nutritional status relative to males.
Keywords: I31; O15; Q18; 330; food security; anthropometrics; gender discrimination; Ernährung; Geschlechterdiskriminierung; Entwicklungstheorie; Vietnam